Forecasting Natural Gas: A Literature Survey - Tamba, Jean Gaston; Essiane, Salomé Ndjakomo; Sapnken, Emmanuel Flavian; Koffi, Francis Djanna; Nsouandélé, Jean Luc; Soldo, Bozidar; Njomo, Donatien (International Journal of Energy Economics and Policy, 2018)
This work presents a state-of-the-art survey of published papers that forecast natural gas production, consumption or demand, prices and income elasticity, market volatility and hike in prices. New models and techniques that have recently been applied in the field of natural gas forecasting have discussed with highlights on various methodologies, their specifics, data type, data size, data source, results and conclusions. Moreover, we undertook the difficult task of classifying existing models that have been applied in this field by giving their performance for instance. Our objective is to provide a synthesis of published papers in the field of natural gas forecasting, insights on modeling issues to achieve usable results, and the future research directions. This work will help future researchers in the area of forecasting no matter the methodological approach and nature of energy source used. Keywords: Forecasting natural gas; Existing forecasting models; Models categorization. JEL Classifications: C53, Q4, Q47